Argentinopanorpa miguezi gen. et sp. nov.: first record of Triassic Mecoptera (Permochoristidae) from the Cuyo Basin (Mendoza, Argentina) - Lara, Maria Belén (2015)
A new genus and species of Permochoristidae, Argentinopanorpa miguezi, is described based on a complete forewing from the Upper Triassic Potrerillos Formation (Mendoza Province, Argentina). The new taxon is placed in the subfamily Agetopanorpinae and distinguished from other genera by the following combination of characters: Rs+MA with six branches, MP with eight branches (MP1 and MP3 with additional forks), CuA and MP fused basally for a short distance. This is the first record of Permochoristidae in the Triassic of South America and the first formal description of Mecoptera for the Cuyo Basin. Previously reported taxa attributed to Mecoptera from the Triassic of South America are briefly discussed with notes on their systematic position.